Field Report on Municipal Road Construction in Kenya and Nigeria: The Politics of Infrastructure Development - Yakubu, Moses; Attoh, Franca (Municipal Road Construction in Kenya and Nigeria: Investigating the Politics of Infrastructure Development, 2021)
Powerpoint presentation for pilot study
Keywords: Municipal engineering; Construction; Infrastructure (Economics); Marginalised Communities; Infrastructure Development; Municipal Road; Nigeria; Kenya